Normativa sobre movilidad humana en el caso particular de los derechos de los refugiados, en el cantón Machala, periodo 2013. - Aquino Maza, Orly Gabriel (2015)
Titling this paper was developed under the central objective determine whether there inapplicability of regulations on human mobility that helps in the particular case of the rights of refugees, for which the fair context will be analyzed from the 2008 Constitution. To pursue this objective an analysis of the Ecuadorian legislation is addressed, in terms of integration and human mobility and the different aspects related to refugees in this country. The main issues addressed in this work titration are related to problems concerning the inapplicability of the rules on human mobility in the case of the rights of refugees, for which a study of integration policies is addressed as Lao international treaties, Constitution of the Republic of Ecuador and the Organic Law of Equality Councils. The principles and rights they refugees, without neglecting the socioeconomic status of the Ecuadorian population and its possible implications in the development are recognized. The intervention proposal involves a reform that is attached to the constitution and international instruments, but it is problematic mediate the matter of the investigation.